Young Women's Reasons to Seek Sexually Transmitted Infection Screening. Issue 5 (28th April 2014) - Backonja, Uba; Royer, Heather R.; Lauver, Diane R.
Abstract Objectives To describe young women's reasons to seek and not to seek sexually transmitted infection (STI) screening; to explore whether reasons differed by age and STI screening history. Design and Sample Cross‐sectional, descriptive. Female students (N = 216) at a university in the Midwestern United States. Measures An anonymous online survey was designed based on the Theory of Care Seeking Behavior and literature regarding STI screening among young women. Results The most common reason to seek STI screening was to start treatment promptly (85%); the most common reason not to seek screening was being asymptomatic (54%). Participants' reasons differed by age and screening history. Women under 25 were more likely than women 25 and older to seek screening because of encouragement from female role models (p < .01). Women who had never been screened were more likely than women who had been screened to avoid screening because of embarrassment (p < .05). Novel findings included seeking STI screening because it "should be done" if sexually active and because of encouragement from female role models. Conclusions Health care and public health professionals can use these findings to develop strategies to improve STI screening rates among young women.